ISLAM AND THE ARAB AWAKENING - Yoyo Yoyo (Universitas Gadjah Mada, 2013)
The Arab awakening has clearly not been the work of Islamist movements.Neither in Tunisia or Egypt, nor in Jordan, Libya, or Syria were they theinisiators. The mass movements took to the streets without them, againtsthe will of their leadership, and, in any event, without their agreement